Pengaruh Benih Subsidi Terhadap Produksi Usahatani Padi Sawah di Desa Pakkabba Kecamatan Galesong Utara Kabupaten Takalar - Mursyid Efendi; Mohammad Natsir; Ardi Rumallang (Jurnal Agribis, 2022)
This study aims to determine the effect of subsidized seeds on rice production in Pakkabba Village, North Galesong District, Takalar Regency. The population collection in this study was carried out intentionally or purposively, namely rice farmers in Pakkabba Village. Meanwhile, for the determination of the sample is done by random sampling that is randomly taking 30 respondents from a population of 300 rice farmers. Data analysis used linear regression data analysis. The results showed that subsidized seeds had a positive effect on rice production in Pakkabba Village. The results of multiple linear regression analysis showed that the type of seed used, the use of fertilizer, and labor had a positive and significant effect on rice production in Pakkabba Village, North Galesong District, Takalar Regency.